MAKNA KONOTATIF GAYA BAHASA METAFORA DALAM KUMPULAN CERPEN SENYUM KARYAMIN KARYA AHMAD TOHARI - Desi Denni Uli Sitinjak; Sumiharti Sumiharti (Universitas Batanghari, 2020)
This research identifies literary work in the form of short story. The aim of this research is to describe connotative meaning of metaphor figurative language on Kumpulan Cerpen Senyum Karyamin Karya Ahmad Tohari. This research is qualitative descriptive with structural approach. The data of this research is sentences which contains metaphor figurative language on Kumpulan Cerpen Senyum Karyamin Karya Ahmad Tohari. The source of the data is Kumpulan Cerpen Senyum Karyamin by Ahmad Tohari. Based on the result of the analysis, it can be concluded that there are 43 expressions which is found on 13 titles of Kumpulan Cerpen Senyum Karyamin Karya Ahmad Tohari. Those expressions have connotative meaning such as “burung nakal” which means “burung yang menganggu”, word “bisu” which means “tidak dapat berkata apa-apa”, “semangatnya rontok” which means “tidak bersemangat”. Based on those 13 titles analysis, it can be concluded that Senyum Karyamin is a short story which dominantly uses connotative metaphor of figurative language which implies someone’s life with hard-work while Orang-orang Sebrang Kali implies that a human is like a chicken with its worse habit, and does not really use connotative metaphor of figurative language.